A little respect: Swearing, police and criminal justice discourse - Methven, E (2018)
© The Author(s) 2018. This article interrogates a commonly articulated idea in relation to the criminalisation of offensive language: namely, that swearing at police challenges their authority and thereby deserves criminal punishment. Drawing on critical discourse analysis, the article examines representations of swearing at police officers in offensive language cases and parliamentary debates, including constructions of power, authority and order. It contributes to—but also denaturalises—conceptions about police power and authority in the context of public order policing. The article argues that criminal justice discourse plays a significant and often under‐acknowledged role in naturalising the punishment of swearing at, or in the presence of, police officers